Case Report: de novo in-frame deletion in PLCG2 gene: a case report of B-cell lymphopenia, pulmonary bullae, and cutis laxa - Wu, Xiaoqi; Zhang, Jingyuan; Shen, Min (Frontiers in Immunology, 2025)
Phospholipase C gamma 2 (PLCG2) gene mutations might cause PLCG2-associated antibody deficiency and immune dysregulation (PLAID)/autoinflammation and PLCG2-associated antibody deficiency and immune dysregulation (APLAID) syndrome. They are two forms of autosomal-dominant immune dysregulation (ID). APLAID patients are usually characterized by skin lesions, pulmonary involvement, and musculoskeletal, ophthalmic, and gastrointestinal tract symptoms, but unlike PLAID patients, these patients do not present with cold urticaria or autoimmunity. Here, we report a 25-year-old man with B-cell lymphopenia, pulmonary bullae, recurrent sinopulmonary infections, and cutis laxa but without cold-induced urticaria. Anti-nuclear antibodies were negative. Trio whole-genome sequencing revealed a de novo heterozygous PLCG2 gene (NM_002661.5) variant c.3417_3419del, p.E1139del, located on chromosome chr16-81973600-81973602. Our findings expand the variety of clinical and genetic phenotypes for APLAID and suggest that this variant would be meaningful.